A note on geographic and seasonal fluctuations in the isotopic composition of baleen in four North Atlantic right whales (Eubalaena glacialis) - Summers, Erin L.; Estrada, James A.; Zeeman , Stephan I. (J. Cetacean Res. Manage., 2023)
Despite management efforts, studies suggest that the North Atlantic right whale (Eubalaena glacialis) population may still be in decline. Due to its endangered status and propensity for human interactions, it is critical that all habitats and migratory routes utilised by the right whale are identified and protected. We conducted incremental stable isotope analysis along the baleen plates of three North Atlantic right whales, an adult female, a juvenile male and a neonate male, showing seasonal oscillation patterns in d15N and d13C values associated with migrations between summer and winter habitats. The d15N and d13C values displayed seasonal variability with enriched values occurring in the winter and depleted during the summer. Comparisons with published values for a fourth adult female (NEAq1014) showed that summer values differed significantly between adults. While the small sample size prevents firm conclusions, these data suggest differential habitat use between adult individuals as well as age classes. Isotopic ratios from plankton in the Labrador Sea indicate that portions of the population may be utilising this habitat as an alternative summer feeding ground.